Structure and Composition of Urban Forest Stands of Pulau Bungin, Teluk Kuantan City, Kuantan Singingi District - Pebriandi, Pebriandi; Suhardianto, Suhardianto; Yoza, Defri (Jurnal Biologi Tropis, 2025)
The existence of urban forests should be referred to as a place to preserve the environment, seeing from the start of the density of settlements that cause less and less space as a place to preserve the environment. The Bungin Island City Forest area in Koto Teluk Kuantan Village is one of the potential tourist destination objects to be offered when tourists visit Jalur City. The aim of this research was to examine the structure and composition of the stands in the Bungin Island City Forest, located in Kuantan Singingi Regency. The research method used systematic sampling method by collecting data directly at the research location. Variables observed were the number of individuals, diameter and height of trees. Vegetation data collection was carried out using the creation of a square plot unit measuring 20 m x 20 m with the determination of the plot location using systematic sampling with random start, namely taking sample plots systematically and randomly started. The data that has been obtained is analyzed descriptively quantitative which is done to obtain a clear picture of the state of the urban forest. The results of the study obtained 23 plant species in the urban forest of Bungin Island with the highest importance value index (INP) is duku plant with a value of 47,10 at the tree level, which means that this plant is the dominant species in the urban forest of Bungin Island. The conclusion of this study shows that the urban forest of Bungin Island is composed of 23 species grouped in 20 families and the composition of the stand is composed of 228 plants with the highest canopy statification in stratum C (subcanopy) followed by stratum B (canopy), stratum D (understory) and stratum A (emergent).